Paediatric Maxillofacial Trauma: An Integrated Approach to Imaging, Dental Care, and Therapeutic Management - Al-Anazi, Saad Ali Awad; Itedal Yousef Ahmed Al-Butyan; Sokaina Yousef Al-Butyan; Zahra Saud Al-Faraj; Talal Hamoud Alhazmi; Ghaith Abdullah Al-Sumait; Khloud Abdulrahman Alhassan Alhafaf; Abdulrahman Yahya Ali Nukhayfi (Saudi Journal of Medicine and Public Health, 2025)
<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Background:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Paediatric maxillofacial trauma is a significant source of morbidity in children, occurring during critical periods of craniofacial growth. Its incidence is rising in many developing nations due to factors like increased motorization and interpersonal violence. Managing these injuries is complex due to the unique anatomical and developmental considerations of the paediatric facial skeleton. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Aim:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> This study aimed to characterize the epidemiology, injury patterns, and management outcomes of paediatric maxillofacial trauma in a cohort of 225 patients over a five-year period (2017-2022), and to compare findings with existing international literature. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Methods:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> A detailed observational study was conducted, analyzing demographic data, mechanisms of injury, clinical presentation, and treatment modalities. Statistical analyses, including chi-square tests, were used to identify significant associations between variables such as age, cause of injury, and injury type. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Results:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> The study found a male predominance (2:1 ratio) and identified self-fall (45%) as the most common cause. A significant finding was that 40% of patients experienced loss of consciousness, highlighting associated head injury risks. Soft-tissue injuries (58%) were most frequent, followed by dentoalveolar (30%) and mandibular fractures (20%). Conservative management was employed in 86% of cases, while open reduction and internal fixation (ORIF) was the primary surgical approach (62% of operative cases). Significant statistical associations were found between patient age and the cause of injury, as well as the type of soft- and hard-tissue injuries sustained. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Conclusion:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> The findings underscore the need for a vigilant, multidisciplinary approach that includes prompt neurological assessment, addresses delays in presentation, and employs age-specific, often conservative, management strategies to preserve long-term craniofacial growth and function.